Ajaran Pokok Mu’tazilah dan Pengaruhnya Pada Kejayaan Umat Islam Zaman Klasik - Yuyu Krisdiyansah; Arif Rahman Hakim (AL-MUFASSIR, 2022)
The Mu'tazilah was born as a reaction to the debate between the Khawarij and the Murjiah. The Mu'tazilah with their rational arguments try to answer various problems with a rational approach. In order to strengthen their argument, the Mu'tazilite figures brought ancient Greek philosophical thought into the realm of Islam. This is what changed the Mu'tazilite perspective on reason and revelation, which initially acted as a reinforcement of Revelation or Nash al-Qur'an and hadith, then since then the position has been reversed, logic is being the first source of argument in answering various problems, while al The Qur'an and hadith are used as reinforcement for rational arguments. This is also what distinguishes the Mu'tazilah from other schools of kalam so that they are often referred to as Islamic rationalists. This rationalist thought was the result of the contact of the Greek intellectual tradition with Islamic teachings through the translation of various Greek books into Arabic during the heyday of the Abbasid Daula so that prominent Muslim thinkers (philosophers) such as Al-Kindi, Alfarabi, Ibn Sina and Ibn Rushd.